An interpretation of the Nazi legal system according to the Sociology of Law of Eugen Ehrlich - Naranjo Jacome,Marko Antonio (2023)
Neither did Hitler abhor the law, nor the legal profession. What Hitler abhorred was the law and legal profession that were not aligned to his worldview. So critical was the law, the legal order, the legal profession to Hitler that he himself, for instance, commenced to construct his regime thanks to the Article 48 of the Weimar Constitution. This work is both an examination and an interpretation of the Nazi legal system. Examination that will rely on the data existing on the records of one of the Nuremberg Trials: ‘The Justice Case’. And, interpretation that will be based on the socio-legal theory of Eugen Ehrlich, considered the founding father of modern Sociology of Law. Fundamental ideas of Ehrlich’s socio-legal approach such as the genesis of state law, social associations and the inner order thereof are herein connected to elements proper to the Nazi law such as the Fuhrer principle and the People’s Court. Further, this thesis demonstrates that the Nazi legal system was a reflection of the inner order of the National Socialist German Workers’ Party. Hence, not only did the judicial system in the administration of justice have to apply Nazi state law, but also norms of conduct that were proper to the Nazi cosmovision. Thus, this work is a contribution to Sociology of Law, specifically to the approach of Eugen Ehrlich; to the study of the law, of fascism, of dictatorship, and of the never-ending ill of humankind: totalitarianism.
Keywords: Nazi legal system; associations; judicial system; law; Nazi association; socio-legal.